Safety and efficacy of HIV Pre-Exposure Prophylaxis (PrEP): an overview of systematic reviews (Research, Society and Development, 2022)
The present study carried out a survey of the safety and efficacy profile of HIV Pre-Exposure Prophylaxis, through an overview of systematic reviews. The bibliographic search was carried out with data published until September 10, 2021, in PubMed, Scopus Elsevier, SciELO and Cochrane databases, according to the PRISMA and Cochrane recommendations. After the identification, screening and eligibility steps, performed by two independent reviewers, six articles met the requirements and were included in the final synthesis. Data demonstrated that all PrEP regimens significantly reduced the risk of acquiring HIV compared to placebo and non-PrEP users, with efficacy dependent on adherence profile, reaching a 96% reduction in infection risk. Adverse events were similar between the PrEP and placebo/non-PrEP groups. Cases of drug-resistant HIV infection occurred among PrEP users who started therapy when they were acutely infected, but the incidence of acquiring drug-resistant HIV while using PrEP was low. Furthermore, there was no association between PrEP use and changes in risky sexual behavior. Thus, it is possible to conclude that this therapy presented a good safety and efficacy profile, thus, the promotion of actions that contribute to its expansion as a public health promotion policy, can reduce the number of new HIV infections and improve the quality of life of individuals at high risk of acquiring this virus.